2022
DOI: 10.1155/2022/3408660
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Interhemispheric Functional Connectivity and Its Associations with Clinical Correlates following Traumatic Brain Injury

Abstract: Objective. To explore the interhemispheric functional coordination following traumatic brain injury (TBI) and its association with posttraumatic anxiety and depressive symptoms. Methods. This was a combination of a retrospective cohort study and a cross-sectional observational study. We investigated the functional coordination between hemispheres by voxel-mirrored homotopic connectivity (VMHC). Grey matter volumes were examined by voxel-based morphometry (VBM), and microstructural integrity of the corpus callo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Strong homotopic rsFC has also been found in the middle occipital gyrus (MOG), inferior parietal lobule (IPL), precentral gyrus (preCG), middle frontal gyrus (MFG), inferior temporal gyrus (ITG), superior temporal gyrus (STG), and anterior insula (aINS) across different tasks (Toro et al ., 2008 ). Homotopic interhemispheric rsFC can be extensively reduced by traumatic brain injury (Li et al ., 2017a ; Mäki-Marttunen et al ., 2013 ; Ovadia-Caro et al ., 2012 ; Raizman et al ., 2022 ; Song et al ., 2022 ) and predict the degree of consciousness or coma severity in disorders of consciousness (Mäki-Marttunen et al ., 2013 ; Ovadia-Caro et al ., 2012 ). Both animal model (Bukhari et al ., 2018 ) and human (Nir et al ., 2022 ) studies have also reported that loss of consciousness produced by general anesthesia reduces the strength of homotopic interhemispheric rsFC and correspondingly increases hemispheric lateralization.…”
Section: Vmhc Methodology and Functional Importance Of Homotopic Inte...mentioning
confidence: 99%
“…Strong homotopic rsFC has also been found in the middle occipital gyrus (MOG), inferior parietal lobule (IPL), precentral gyrus (preCG), middle frontal gyrus (MFG), inferior temporal gyrus (ITG), superior temporal gyrus (STG), and anterior insula (aINS) across different tasks (Toro et al ., 2008 ). Homotopic interhemispheric rsFC can be extensively reduced by traumatic brain injury (Li et al ., 2017a ; Mäki-Marttunen et al ., 2013 ; Ovadia-Caro et al ., 2012 ; Raizman et al ., 2022 ; Song et al ., 2022 ) and predict the degree of consciousness or coma severity in disorders of consciousness (Mäki-Marttunen et al ., 2013 ; Ovadia-Caro et al ., 2012 ). Both animal model (Bukhari et al ., 2018 ) and human (Nir et al ., 2022 ) studies have also reported that loss of consciousness produced by general anesthesia reduces the strength of homotopic interhemispheric rsFC and correspondingly increases hemispheric lateralization.…”
Section: Vmhc Methodology and Functional Importance Of Homotopic Inte...mentioning
confidence: 99%
“…Recent neuropsychological and neuroimaging literature suggested the vulnerability of the MTG in various aspects of working memory and emotional cognitive perception ( 56 ). Specially, frontotemporal network and brain activity dysfunction in this area has been known to be a target of mTBI which is mainly responsible for cognitive impairment in these patients ( 57 , 58 ). A prior study showed increased functional connectivity between subnetwork nodes in the DMN including the temporal cortex areas in patients with chronic mTBI after 1 year post-injury that was linked with working memory and cognitive dysfunction in those patients ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Resting-state functional magnetic resonance imaging (rs-fMRI) has been widely used in neuroscience for detecting intrinsic brain functional architecture as well as interactions between and within neural networks as the biomarkers of cognitive and neurological disorders ( Jeter et al, 2013 ; Sours et al, 2015 ). Various approaches have been proposed for analyzing rs-fMRI data in mTBI cohorts including independent component analysis (ICA) ( Bittencourt-Villalpando et al, 2021 ), graph theory ( van der Horn et al, 2017 ), seed-based FC ( Madhavan et al, 2019 ; Lemme et al, 2021 ; Philippi et al, 2021 ), amplitude of low-frequency fluctuation (ALFF), regional homogeneity (ReHo) ( Zhan et al, 2015 ; Vedaei et al, 2021 ), degree centrality (DC) ( Li et al, 2019 ), voxel-mirrored homotopic connectivity (VMHC) ( Puig et al, 2020 ; Song et al, 2022 ). The growing body of studies of functional neuroimaging of the resting brain has shown that mTBI is accompanied by alterations of resting-state functional connectivity between and within intrinsic brain networks including the default mode network (DMN), fronto-parietal, motor, dorsal attention, and visual networks ( Shumskaya et al, 2012 ; Stevens et al, 2012 ; Zhou et al, 2012 , 2014 ; Dall’Acqua et al, 2017 ; Palacios et al, 2017 ; Liu et al, 2018 ; Li et al, 2019 ; Madhavan et al, 2019 ; Meier et al, 2020 ; Song et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been proposed for analyzing rs-fMRI data in mTBI cohorts including independent component analysis (ICA) ( Bittencourt-Villalpando et al, 2021 ), graph theory ( van der Horn et al, 2017 ), seed-based FC ( Madhavan et al, 2019 ; Lemme et al, 2021 ; Philippi et al, 2021 ), amplitude of low-frequency fluctuation (ALFF), regional homogeneity (ReHo) ( Zhan et al, 2015 ; Vedaei et al, 2021 ), degree centrality (DC) ( Li et al, 2019 ), voxel-mirrored homotopic connectivity (VMHC) ( Puig et al, 2020 ; Song et al, 2022 ). The growing body of studies of functional neuroimaging of the resting brain has shown that mTBI is accompanied by alterations of resting-state functional connectivity between and within intrinsic brain networks including the default mode network (DMN), fronto-parietal, motor, dorsal attention, and visual networks ( Shumskaya et al, 2012 ; Stevens et al, 2012 ; Zhou et al, 2012 , 2014 ; Dall’Acqua et al, 2017 ; Palacios et al, 2017 ; Liu et al, 2018 ; Li et al, 2019 ; Madhavan et al, 2019 ; Meier et al, 2020 ; Song et al, 2022 ). However, most of the studies were performed at the group level analysis which makes it challenging to generalize the findings to the identification of mTBI findings in individuals.…”
Section: Introductionmentioning
confidence: 99%